SITUS MAKAM KUNA ISLAM JERA’ LOMPOE DAN STRATIFIKASI SOSIAL DI SOPPENG - nfn Muhaeminah (Balai Arkeologi Provinsi Sulawesi Selatan, 2001)
Soppeng is one of the kingdoms that related with Suppaq, Luwu, Bone, Tanete, and Wajo kingdoms. The relationship was proved by the existence of Soppeng outsiders tombs, on ancient Islamic tombs of Jera' Lompoe. It was acknowledge from tombs size, types or its gravestone that they came from